PENGARUH KINERJA KEUANGAN, KINERJA SOSIAL DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN YANG DIMODERASI OLEH TUJUAN PEMBANGUNAN BERKELANJUTAN PADA PERUSAHAAN BUMN DI INDONESIA - Sutrisno Sutrisno; Iskandar Muda; Azizul Kholis (Transpublika Publisher, 2024)
This research aims to analyze the influence of financial performance, social performance and environmental performance on company value in state-owned companies in Indonesia. Apart from that, this research also aims to find out whether sustainable development goals can moderate this model. The research design uses a casual comparative research design, namely investigating possible cause-and-effect relationships using a quantitative approach. The data used is secondary data obtained from state-owned companies for the period 2018 to 2022. The analysis technique used is panel data regression analysis and interaction tests (moderation tests) which are analyzed using the help of the Eviews version 10 application. The results of the research show that financial performance, performance social and environmental performance influence company value. Development objectives moderate environmental performance on company value. However, sustainable development goals cannot moderate financial performance and social performance on company value.